(3GdJhRjY GdeGOj hYfGUQ NOeI GdRHhfs - (3CcQe CMeO QVG(B, (3GdWhjds; (3gVjeI YHO GdhGMO SdWGf GdLfGHj(B, s ((3YeGf(B:s (3OGQ GdMGeO ddfTQ hGdJhRjY(B,s, 2015)
(3GdJhRjY GdeGOj, YfGUQ NOeI GdRHhf , OQGSGJ JJYdb HGdehVhY hefgLjI GdOQGSI, JMdjd hhUa hJTNjU hGbY eJZjQGJ GdOQGSI GdGSJfJGLGJ hGdJhUjGJs
(3GdedGMb U(B.235 (3GdeUGOQ U(B.219s
Keywords: (3COGQI GdeHjYGJs; (3GdJShjbs